La Diffusion Des Contenus Televisuels Et Les Pratiques De Reception Des Spectateurs A L'ere Du Numerique - Honoré, Kahi Oulaï (European Scientific Journal, ESJ, 2016)
The objective is to question broadcasting methods and TV reception practices in the digital area. In this logic, we first adopt a literary review and then an investigation using a questionnaire and a semi-directing talk. The data show that media convergence is conceptualized in its technological and cultural parameters. It is perceived like a change of perspective to figure out the evolution of media and its various uses in terms of broadcasting process and consumption posture. The broadcasting processes concern the exploitation of the multiplicity of screens, methods of publication and the use of sociotechnical devices. The individual and collective practices of consumption vary according to the user's technical and technological skills which induce various viewing postures.